2022
DOI: 10.1021/acsmedchemlett.2c00260
|View full text |Cite
|
Sign up to set email alerts
|

A Warhead Substitution Study on the Coronavirus Main Protease Inhibitor Nirmatrelvir

Abstract: The SARS-CoV-2 pandemic is currently causing an unprecedented global health emergency since its emergence in December 2019. In December 2021, the FDA granted emergency use authorization to nirmatrelvir, a SARS-CoV-2 main protease inhibitor, for treating infected patients. This peptidomimetic is designed with a nitrile warhead, which forms a covalent bond to the viral protease. Herein, we investigate nirmatrelvir analogs with different warheads and their inhibitory activities. In addition, antiviral activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Another approach of enhanced antiviral combat considers alternative warhead chemistries to increase target specificity as well as drug bioavailability and clearance after successful therapy. An example that explores the chemical space around the reactive electrophilic warhead shows promising potential to finetune inhibitor properties to desired parameters solely by exchange of the reactive head group [116]. Aside from the already employed diversity of functional groups, novel chemistries that have the potential to improve target interaction can be derived from wider drug repurposing screens, including, for example, boronic acids, such as in ixazomib [117].…”
Section: Future Strategies/outlookmentioning
confidence: 99%
“…Another approach of enhanced antiviral combat considers alternative warhead chemistries to increase target specificity as well as drug bioavailability and clearance after successful therapy. An example that explores the chemical space around the reactive electrophilic warhead shows promising potential to finetune inhibitor properties to desired parameters solely by exchange of the reactive head group [116]. Aside from the already employed diversity of functional groups, novel chemistries that have the potential to improve target interaction can be derived from wider drug repurposing screens, including, for example, boronic acids, such as in ixazomib [117].…”
Section: Future Strategies/outlookmentioning
confidence: 99%
“…Nirmatrelvir analogues with different warheads and their inhibitory activities were also investigated, suggesting that hydroxymethylketone and ketobenzothiazole warheads can also be employed for treating coronavirus infections equipotent to the nitrile. 58 To clearly characterise differences between structures and biochemical activities, herein we exhibit the structures and cellular/enzymatic IC 50 values of all drugs mentioned above (Table 1).…”
Section: Anti-viralmentioning
confidence: 99%
“…Nirmatrelvir analogues with different warheads and their inhibitory activities were also investigated, suggesting that hydroxymethylketone and ketobenzothiazole warheads can also be employed for treating coronavirus infections equipotent to the nitrile. 58…”
Section: Targeted Covalent Inhibitors and Binding Modesmentioning
confidence: 99%
“…This complex helps in explaining the inhibitory mechanism of nirmaltrevir, as a reversible covalent inhibitor, in which the nitrile warhead joints covalently with the Cys145 side-chain thiol group (Fig. 2), the conformationally restricted Gln and Pro residues occupy the S1 and S2 subsites, respectively, Modification of the nitrile covalent warhead of nirmaltrevir indicated that an aldehyde, a hydroxymethylketone and a ketobenzothiazole group provided potent inhibitors in the isolated enzyme assays, while other less electrophilic groups led to inactive compound [31] .…”
Section: Peptidomimetics As Sars-cov-2 Mpro Inhibitors: First Approvalmentioning
confidence: 99%